Optimization of Activated Carbon Preparation from Date Stones by Microwave Assisted K2CO3 Activation - F. Abbas, Asmaa; J. Ahmed, Muthanna (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The preparation of activated carbon (AC) from date stones by using microwave assisted K2CO3 activation was investigated in this paper. The influence of radiation time, radiation power, and impregnation ratio on the yield and methylene blue (MB) uptake of such carbon were studied. Based on Box-Wilson central composite design, two second order polynomial models were developed to correlate the process variables to the two responses. From the analysis of variance the significant variables on each response were identified. Optimum coditions of 8 min radiation time, 660 W radiation power and 1.5 g/g impregnation ratio gave 460.123 mg/g MB uptake and 19.99 % yield. The characteristics of the AC were examined by pore structure analysis, and scanning electron microscopy (SEM).The BET surface area and total pore volume were indentified to be 1144.25 m²/g and 0.656 m³/g, respectively.